Rancang Bangun Alat Peningkatan Keamanan Pintu Belakang Kendaraan Angkutan Barang - Buang Turasno; M. Feri Ramadhan; Moch. Aziz Kurniawan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Vehicles in Indonesia are an important part of moving people or goods from one place to the destination, one of which is the transportation of boxed goods. However, the lack of security for boxed goods transport vehicles has always been the target of burglary of goods cargo in the area of Jalan Perniagaan Barat Roa Malaka Tambora, West Jakarta, perpetrators of goods theft from boxed goods cars that are traveling. Therefore, it is necessary to have a security system that can notify the driver when the back door of the vehicle is broken into, namely a Security Detection Tool on Iot-Based Goods Transport Vehicles Using Telegram this tool is able to detect the movement of the thief and evidence will be sent via Telegram. The research method used in this research is research adopting the ADDIE model R&D method, namely Analysis, Design, Development, Implementation, and Evaluation (assessment) of the reference model (ADDIE). In implementing the design of a Security Detection Tool on Iot-Based Goods Transport Vehicles Using Telegram Using the Esp32 Cam Microcontroller, MCU Node, and PIR sensors. Based on the Security Detection Tool, the transportation of box goods works well. Using the PIR Sensor, which is tested and applied directly to the vehicle. The tool is capable of sending telegrams in the form of messages, locations, and photos of the break-in.